2016
DOI: 10.1177/0267659116683791
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiopulmonary bypass surgery on cytokines in epicardial adipose tissue: comparison with subcutaneous fat

Abstract: One of the most relevant findings of this study was the marked decrease in EAT levels of TNF-α, AFABP, leptin and adiponectin after the CPB termination. Our results suggest that EAT might serve as a pool of cytokines which are released into the circulation in reaction to surgery with CPB. Should these novel findings be confirmed, new strategies to assess and possibly reduce EAT contribution on adverse outcomes of cardiac surgery may be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…This can increase neointimal inflammation and plaque formation. Some studies have suggested that cytokines and adipocytokines derived from EAT increase lymphocyte, macrophage, and mast cell activities around perivascular adipose tissue [21]. Furthermore, macrophages migrating into plaques via the vasa vasorum and surrounding perivascular adipose tissue become a source of foam cells, which are involved in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This can increase neointimal inflammation and plaque formation. Some studies have suggested that cytokines and adipocytokines derived from EAT increase lymphocyte, macrophage, and mast cell activities around perivascular adipose tissue [21]. Furthermore, macrophages migrating into plaques via the vasa vasorum and surrounding perivascular adipose tissue become a source of foam cells, which are involved in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, the perivascular adipose tissue that surrounds the coronary arteries, promotes the expression of a proinflammatory phenotype and the accumulation of epicardial adipose tissue is closely associated with the presence, severity, and progression of coronary artery disease independently from visceral obesity [103][104][105][106][107][108][109][110]. This illuminates why NAFLD is known to be associated with various markers of subclinical atherosclerosis including coronary artery calcification and increased coronary-artery calcium score, independently from traditional CVD risk factors and metabolic syndrome features [27,87,111].…”
Section: Nafld and Coronary Artery Diseasementioning
confidence: 99%
“…159,163 Furthermore, the premise that an expanded epicardial fat mass is biologically abnormal is supported by the analyses of tissue obtained during surgery and by the finding of an elevated transcardiac gradient for proinflammatory adipocytokines in states of epicardial adiposity. [164][165][166][167] Yet, the intimacy of epicardial fat and the myocardium can be bidirectional; conceivably, epicardial adipose tissue expansion may reflect the extension of inflammation originating in the heart to the epicardium. If so, then increases in epicardial fat would represent a biomarker rather than a cause of cardiac inflammation.…”
Section: Challenges In Assessing the Role Of Epicardial Adipose Tissumentioning
confidence: 99%
“…Nevertheless, epicardial fat depots (as well as intramyocardial lipids) are unique in their exceptionally close proximity to the myocardium, and fat expansion adjacent to cardiomyocytes may be particularly linked to cardiac derangements 159,163 . Furthermore, the premise that an expanded epicardial fat mass is biologically abnormal is supported by the analyses of tissue obtained during surgery and by the finding of an elevated transcardiac gradient for proinflammatory adipocytokines in states of epicardial adiposity 164–167 . Yet, the intimacy of epicardial fat and the myocardium can be bidirectional; conceivably, epicardial adipose tissue expansion may reflect the extension of inflammation originating in the heart to the epicardium.…”
Section: Deleterious Biological Transformation Of Epicardial Adipose Tissue In Systemic Inflammatory and Metabolic Disordersmentioning
confidence: 99%